(untitled) (translation. a transdisciplinary journal, 2022)
In every possible sense, translation is necessary but impossible. Melanie Klein, the Viennese psychoanalyst whom the Bloomsbury Group killed with kindness, suggested that the work of translation is an incessant shuttle that is a ‘life’. The human infant grabs on to some one thing and then things. This grabbing (begreifen) of an outside indistinguishable from an inside constitutes an inside, going back and forth and coding everything into a sign-system by the thing(s) grasped. One can call this crude coding a ‘translation’.